Soil organic matter availability and climate drive latitudinal patterns in bacterial diversity from tropical to cold temperate forests. (7th September 2017) - Tian, Jing; He, Nianpeng; Hale, Lauren; Niu, Shuli; Yu, Guirui; Liu, Yuan; Blagodatskaya, Evgenia; Kuzyakov, Yakov; Gao, Qun; Zhou, Jizhong
Abstract: Bacteria are one of the most abundant and diverse groups of micro‐organisms and mediate many critical terrestrial ecosystem processes. Despite the crucial ecological role of bacteria, our understanding of their large‐scale biogeography patterns across forests, and the processes that determine these patterns lags significantly behind that of macroorganisms. Here, we evaluated the geographic distributions of bacterial diversity and their driving factors across nine latitudinal forests along a 3, 700‐km north–south transect in eastern China, using high‐throughput 16S rRNA gene sequencing. Four of 32 phyla detected were dominant: Acidobacteria, Actinobacteria, Alphaproteobacteria and Chloroflexi (relative abundance > 5%). Significant increases in bacterial richness and phylogenetic diversity were observed for temperate forests compared with subtropical or tropical forests. The soil organic matter (SOM) mineralisation rate (SOMmin, an index of SOM availability) explained the largest significant variations in bacterial richness. Variation partition analysis revealed that the bacterial community structure was closely correlated with environmental variables and geographic distance, which together explained 80.5% of community variation. Among all environmental factors, climatic features (MAT and MAP) were the best predictors of the bacterial community structure, whereas soil pH and SOMmin emerged as the most important edaphic drivers of the bacterial community structure. Plant functional traits (community weighted means of litter N content) and diversity resulted in weak but significant correlations with the bacterial community structure. Our findings provide new evidence of bacterial biogeography patterns from tropical to cold temperate forests. Additionally, the results indicated a close linkage among soil bacterial diversity, climate and SOM decomposition, which is critical for predicting continental‐scale responses under future climate change scenarios and promoting sustainable forest ecosystem services. A plain language summary is available for this article. Abstract : Plain Language Summary